Double-armed cone-shaped flexoelectric transducer - Zheng, Jianfeng; Liang, Ke; Lin, Zhenyuan; Di, Hao; Cheng, Yong (Frontiers in Physics, 2023)
Compared with a single energy harvester, this tuning fork double-armed cone-shaped flexure transducer can fundamentally solve the problems of high resonance frequency, low output efficiency, and narrow bandwidth of the flexure transducer. Since the transducer limits the clamping losses of the cantilever beam, it provides sufficient stiffness-mass balance to lower the resonance frequency of the system and extend the bandwidth. The tapered structure provides sufficient strain gradient for the flexoelectric effect, improving the output efficiency of the whole system. The vibration frequency of the tuning fork structure and the derivation of the bandwidth formula are analyzed theoretically, and then the electrode width and thickness of the cone structure are studied through simulation to analyze the transducer output response, resonant frequency, bandwidth, and output impedance.